Study on epilithic diatoms in the kozluk creek (Arapgir-Malatya, Turkey) - Pala, G.; Caglar, M.; Selamoglu, Z. (Iranian Fisheries Science Research Inst-Ifsri, 2017)
[Abstract Not Available]
Keywords: Kozluk Creek; Diatom; Epilithic; Algae